A cross-sectional study of the mental health burden among COVID-19 survivors - Arvind Nongpiur; Bhupen Barman; Kimberly Syiem; Andreecia Mn Mawiong; Naveen Anand; Arvind Nune (Indian Journal of Psychiatry)
Introduction: Coronavirus disease 2019 (COVID-19) pandemic has had a significant impact on mental health, including stress, anxiety, and depression. This study aimed to assess the incidence and severity of mental health issues among individuals diagnosed with COVID-19 infection. Methods: A semi-structured proforma for socio-demographic and clinical parameters was used to collect cross-sectional hospital-based data of subjects who tested positive for COVID-19 infection. The Modified Fatigue Impact Scale (MFIS), Hospital Anxiety and Depression Scale (HADS), and Perceived Stress Scale (PSS) were used to assess the presence of physical, psychological, and cognitive symptoms. The presence of anxiety, depression, and stress was based on the cut-off scores for HADS-A (≥8), HADS-D (≥8), and PSS (≥14), respectively. Results: A total of 101 patients comprising 39 (38.6%) males were recruited. Compared to nuclear families, we observed that patients living in joint families had significantly greater severity scores for fatigue [MFIS (p = 0.04)], anxiety [HADS-A (p = 0.004)], depression [HADS-D (p = 0.004)], and stress [PSS (p = 0.02)]. Based on the cut-off scores, we found that 44 (43.6%) patient had anxiety, 41 (40.6%) had depressive, and 72 (71.3%) had moderate to high stress symptoms, respectively. We also observed significantly greater fatigue and anxiety scores, that is, MFIS (p = 0.008) and HADS-A (p = 0.03) in those who received oxygen therapy compared to those who did not. The subjects who received corticosteroids were older (p = 0.01) and had significantly higher stress scores [PSS (p < 0.001)]. The study showed that patients who were assessed more than 3 months post-COVID-19 infection had higher fatigue and depression scores; however, the difference did not reach statistical significance (MFIS P = 0.058; HADS P = 0.059). Conclusion: Our study confirms that COVID-19 infection can cause various adverse mental health issues. Mitigating the hazardous effects of COVID-19 pandemic on mental health should be a top priority for public health to prevent long-term complications.